Intraoperative cardiovascular collapse in a patient with epidermolysis bullosa - Ozer, Ayse Belin; Aksu, Ahmet; Karatepe, Umit; Altun, Aysun Yildiz (Elsevier Science Inc, 2016)
[Abstract Not Available]